2014
DOI: 10.1021/sc500392k
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Horseradish Peroxidase (I-HRP) as Biocatalyst for Oxidative Polymerization of 2,6-Dimethylphenol

Abstract: Gel Permeation Chomatography (GPC) The molecular weights of synthesized PPO were determined by GPC performed on a Tosoh EcosHLC-8320 Gel Permeation Chromatography apparatus equipped with both refractive index (IR) and ultraviolet (UV) detectors (UV detection, λ = 280 nm) using Tosoh alpha 4000 and 2000 columns and DMF was used as the solvent. Calibration curves were obtained by using polystyrene standards ranging between M n 500-2.89 × 10 6 gmol-1. I-HRP preparation I-HRP was synthesised using previous reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…[26][27][28] We demonstrated that the tyrosine residues of poly(tyrosine-r-lysine) could be converted to 3,4dihydroxyphenylalanine (DOPA) residues through selective oxidation using tyrosinase to develop novel adhesive materials inspired by a natural protein found in mussels. 34,35 Silk materials are candidates for structural materials because of their excellent mechanical properties. 26,27 Horseradish peroxidase (HRP) catalyzes the oxidation of phenolic substrates into radical species in the presence of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] We demonstrated that the tyrosine residues of poly(tyrosine-r-lysine) could be converted to 3,4dihydroxyphenylalanine (DOPA) residues through selective oxidation using tyrosinase to develop novel adhesive materials inspired by a natural protein found in mussels. 34,35 Silk materials are candidates for structural materials because of their excellent mechanical properties. 26,27 Horseradish peroxidase (HRP) catalyzes the oxidation of phenolic substrates into radical species in the presence of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial horseradish peroxidase (HRP) biomimetically oxidized resveratrol, a trihydroxystilben, and the reaction was tuned from decomposition to dimerization by incorporation of various metal ions . Immobilized HRP formed radicals on phenols which reacted to linear polymers via C‐O bridges . In the presence of a slight molar excess of hydrogen peroxide HRP was also the enzyme of choice for the patented production of natural divanillin .…”
Section: Enzyme Catalyzed Routes To Divanillinmentioning
confidence: 99%
“…Horseradish peroxidase (HRP) and other heme peroxidase catalyzed polymerization of phenols and anilines in the presence of hydrogen peroxide is an environmental friendly route to synthesize industrially important polyaromatics . The HRP and related enzymes also catalyze the polymerization of vinylic monomers in the presence of β‐diketones or surfactants under milder conditions …”
Section: Introductionmentioning
confidence: 99%
“…Horseradish peroxidase (HRP) and other heme peroxidase catalyzed polymerization of phenols and anilines in the presence of hydrogen peroxide is an environmental friendly route to synthesize industrially important polyaromatics. [1][2][3] The HRP and related enzymes also catalyze the polymerization of vinylic monomers in the presence of β-diketones or surfactants under milder conditions. [4,5] However, these enzymes show low stability under non − physiological conditions, and are relatively expensive, whereas metalloporphyrins are stable, inexpensive and relatively more promising for various applications.…”
Section: Introductionmentioning
confidence: 99%